Zoborg: On‐Demand Climbing Control for Cyborg Beetles - Lachlan Fitzgerald; H. Nhan Le; Robbie S. Wilson; H. Duoc Nguyen; Thanh Nho Do; T. Thang Vo‐Doan (Advanced Science)
Abstract Transitioning from horizontal surfaces to vertical walls is crucial for terrestrial robots to navigate complex environments. Replicating such impressive surface transitions in artificial insect‐scale robots has been particularly challenging. Here, innovative control schemes are introduced that enable ZoBorg (a cyborg beetle from Zophobas morio) to successfully climb walls from horizontal planes. The flex‐rigid structure, flexible footpads, sharp claws, and embedded sensors of the living insect enable ZoBorg to achieve agile locomotion with exceptional adaptability, all at low power and low cost. ZoBorg crosses low‐profile obstacles (5 and 8 mm steps) with a success rate exceeding 92% in less than one second. Most importantly, electrical stimulation of the elytron enables Zoborg to transition onto vertical walls with a success rate of 71.2% within 5 s. ZoBorg has potential applications for search and rescue missions due to its ability to traverse complex environments by crossing various obstacles, including low‐profile steps, inclines, and vertical walls.